Reaction of grasses belonging to diverse genera and species to infection by Rhynchosporium oryzae - Prabhu, Anne Sitarama; Bedendo, Ivan Paulo (Pesquisa Agropecuaria Brasileira, 2014)
The degree of resistance and type of reaction to infection caused by Rhynchosporium oryzae was studied in 32 grasses belonging to 18 genera and 11 species of Oryza (O. sativa. O. glaberrima, O. longistaminata, O. barthil, O. officinalis, O. ridleyi, O. brachyantha, O. eichingeri, O. latifolia, O. stapfii, O. australiensis. Inoculations were made with mycelial discs of fungi on leaves of 50 – day old plants in glasshouse, All the species belonging to Oryza were suceptible. However, distinct reactions differentiating resistance and susceptibility between the gramineous plants belonging to other genera were evident. Four reaction types were identified: immune; resistant (top leaves immune, lower leaves with lesions restricted to the point of inoculation); moderately resistant (top leaves with lesions restricted to the point of inoculation and lower leaves with elongated lesions); susceptible (all leaves with alongated lesions). While different species belonging to genera Andropogon, Digitaria, Hyparrhenia. Paspalum, Cenchnis, Tripsacum, Brachiaria, Cynodon, Echinochloa, Panicum e Pennisetum were moderately resistante, resistant, or immune, Chloris sp., Echinaloena sp., Eleusine sp.,Melinis sp.,Rhynchelytrum sp., Setaria, Oryza spp. showed suceptible reaction. The results demonstrated that within the same genus, all the species exhibited either suceptible or different degrees of resistant reaction, indicating thereby that the differences were intergeneric.
Keywords: leaf scald; rice; resistance; host-range